Polychlorinated Biphenyl (PCB)-Degrading Potential of Microbes Present in a Cryoconite of Jamtalferner Glacier - Weiland-Bräuer, Nancy; Fischer, Martin A.; Schramm, Karl-Werner; Schmitz, Ruth A. (Frontiers in Microbiology, 2017)
Aiming to comprehensively survey the potential pollution of an alpine cryoconite (Jamtalferner glacier, Austria), and its bacterial community structure along with its biodegrading potential, first chemical analyses of persistent organic pollutants, explicitly polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) as well as polycyclic aromatic hydrocarbons (PAHs), revealed a significant contamination. In total, 18 PCB congeners were detected by high resolution gas chromatography/mass spectrometry with a mean concentration of 0.8 ng/g dry weight; 16 PAHs with an average concentration of 1,400 ng/g; and 26 out of 29 OCPs with a mean concentration of 2.4 ng/g. Second, the microbial composition was studied using 16S amplicon sequencing. The analysis revealed high abundances of Proteobacteria (66 %), the majority representing α-Proteobacteria (87 %); as well as Cyanobacteria (32 %), however high diversity was due to 11 low abundant phyla comprising 75 genera. Biodegrading potential of cryoconite bacteria was further analyzed using enrichment cultures (microcosms) with PCB mixture Aroclor 1242. 16S rDNA analysis taxonomically classified 37 different biofilm-forming and PCB-degrading bacteria, represented by Pseudomonas, Shigella, Subtercola, Chitinophaga and Janthinobacterium species. Overall, the combination of culture-dependent and culture-independent methods identified degrading bacteria that can be potential candidates to develop novel bioremediation strategies.